PENGARUH SELF-HYPNOSIS PADA MANAJEMEN STRES TERHADAP KUALITAS KEHIDUPAN KERJA PERAWAT POST PANDEMI COVID-19 DI RS X [THE EFFECT OF SELF-HYPNOSIS ON STRESS MANAGEMENT ON THE QUALITY OF NURSING WORK LIFE OF NURSES POST COVID-19 PANDEMIC AT HOSPITAL X] - Setiyawan, Yoel Wahyu; Wijayanti, Catharina Dwiana; Bandur, Agustinus (Universitas Pelita Harapan, 2023)
The COVID-19 pandemic is an emerging global disease that has an impact on health, psychological and physiological aspects and requires nurses to adapt during the post-pandemic period. One of the adaptation techniques so that nurses can improve the quality of family life and post-pandemic work can be done by means of self-hypnosis using motivational audio. Previous studies have shown that self-hypnosis using motivational audio is an effective method that is economical, fast, safe, and can be carried out independently to relieve anxiety and stress-related disorders, but there has been no report whether it has an impact on the quality of nursing work life. This study aims to analyze the effect of stress management with self-hypnosis on the quality of nursing work life of nurses after the COVID-19 pandemic at X Hospital. Quantitative research methods using quasi-experimental nonequivalent control group pre-posttest design. The research sample of 118 nurses was divided into an intervention group and a control group. Respondents were given a self-hypnosis intervention using motivational audio. The measuring instrument is a quality of nursing work life questionnaire. The results showed that there were differences in the effect of self-hypnosis on quality of nursing work life during pre and post intervention in the intervention group (p-value 0.000) and the control group (p-value 1.000). There was no partial effect on the characteristics of nurses during the pre and post intervention in the intervention and controlgroups with a p value > 0.05. There is a simultaneous effect of the age variable on the quality of nursing work life with a p value of 0.001 (p <0.05). Self-hypnosis uses motivational audiobeing a way for nurses of all ages to manage anxiety and stress-related disorders so that they are able to adapt to post-pandemic conditions of COVID-19 so as to improve the quality of nurses' work lives.BAHASA INDONESIA Pandemi COVID-19 merupakan penyakit global emerging yang berdampak pada aspek kesehatan, psikologis, dan fisiologis serta membutuhkan proses adaptasi perawat pada masa post pandemic. Salah satu teknik adaptasi sehingga perawat dapat meningkatkan kualitas kehidupan keluarga dan pekerjaannya post pandemic dapat dilakukan dengan cara self-hypnosis menggunakan audio motivasi. Studi terdahulu menunjukkan self-hypnosis menggunakan audio motivasi merupakan suatu metode efektif yang hemat, cepat, aman, dan dapat dilaksanakan secara mandiri untuk menghilangkan kecemasan dan gangguan terkait stress, namun belum ada laporan apakah berdampak terhadap quality of nursing work life. Penelitian ini bertujuan menganalisis pengaruh manajemen stress dengan self-hypnosis terhadap quality of nursing work life perawat post pandemi COVID-19 di RS X. Metode penelitian kuantitatif menggunakan rancangan quasy experiment nonequivalent control group preposttest design. Sampel penelitian 118 perawat terbagi menjadi kelompok intervensi dan kelompok kontrol. Responden diberi intervensi self-hypnosis menggunakan audio motivasi. Alat ukur berupa kuesioner quality of nursing work life. Hasil penelitian terdapat perbedaan pengaruh self-hypnosis terhadap quality of nursing work life saat pre dan post intervensi untuk kelompok intervensi (p-value < 0,001), kelompok kontrol (p-value 1,000). Tidak ada pengaruh secara parsial karakteristik perawat saat pre dan post intervensi pada subjek dengan nilai p value >0.05. Ada pengaruh secara simultan variabel umur terhadap quality of nursing work life dengan p value 0,001 (p<0,05). Self-hypnosis menggunakan audio motivasi menjadi salah satu cara bagi perawat diberbagai entang usia dalam mengelola kecemasan dan gangguan terkait stress sehingga mampu beradaptasi pada kondisi post pandemic COVID-19 agar dapat meningkatkan kualitas kehidupan kerja perawat.